Type A aortic aneurysm dissection: causes of development, diagnostic methods and treatment results - Kravchenko, I. M.; Kravchenko, V. I.; Zhekov, I. I.; Osadovska, I. A.; Zinovchyk, I.I.; Gorban, D. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Surgical treatment of Type A aortic aneurysm dissection remains one of the most complicated problems in car-diac surgery. The whole surgical treatment experience of such aneurysms by one team is presented in the article. Factors that could have caused the aortic aneurysm (dissection) development are provided. It is shown that experience accumulation, methods improvement of surgical treatment, brain, heart and internal organs protection have allowed to reach the hospital mortality rate of 4.5% over the last 5 years. Data on severe baseline of the operated patients are presented in the paper. It is represented that in the Institute’s experience type A aneurysm dissection accounts for 28.9% of all aneurysms. The vast majority (79.6%) of patients were operated on for acute or subacute type A dissection; 69.2% of patients had type I dissec-tion. All operations were performed under conditions of bypass, moderate hypothermia (30–32 °C) and during the aortic arch replacement (42.4%) – under conditions of deep hypothermia (13–20 °C) and retrograde cerebral perfusion. Surgical correction methods are presented with valve-saving surgeries performed in 63.7% of patients. The surgical treatment results have been shown to be highly dependent on the time of the surgery. Thus, at the initial stage of surgical experience, hospital mortality was 24.1% with a decrease to 16.1% and with a decrease to 4.6% over the last 8 years.